Metal salt-resistant coating structure with low salt water invasion and construction method of metal salt-resistant coating structure

By designing a multi-layer coating structure, using graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating, the existing anti-salt coating materials have high cost and poor adhesion in low brine environments, and the corrosion resistance of high adhesion, long service life and low cost are achieved.

CN119799155AActive Publication Date: 2025-04-11PINGLU CANAL GRP CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411863145.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-11
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing anti-salt coating materials have high cost and poor adhesion in low-brine environments, making it difficult to meet the anti-salt requirement of low-brine invasion metals.

Method used

A metal anti-salt coating structure with low brine intrusion was designed, including a multi-layer coating structure composed of graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating. By collaborating with the thickness and formulation of each coating, a better physical anchoring and chemical bonding effect is formed.

Benefits of technology

The adhesion and bonding force of the coating structure on metal materials is significantly improved, and the service life is extended, while reducing the cost of raw materials, achieving the best balance between optimal corrosion resistance, minimum cost and optimal service life in low-concentration brine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a metal anti-salty coating structure with low salt water invasion and a construction method thereof, and relates to an anti-salty coating material. The coating structure sequentially comprises a bottom layer, a middle layer and a surface layer, wherein the bottom layer is formed by coating and curing a graphene zinc powder coating; the middle layer is formed by coating and curing epoxy resin paint; and the surface layer is formed by coating and curing an acrylic polyurethane coating. According to the coating structure, through targeted design of a coating formula and synergistic cooperation of the thicknesses of all the coatings, better physical anchoring and chemical bonding effects can be formed between all the coatings, so that the adhesive force of the coating structure on a metal material and the binding force between the coatings are remarkably improved, and the service life of the coating structure is remarkably prolonged; meanwhile, conventional raw materials are selected for all the layers of coatings, the sources are wide, the anti-corrosion effect under the low-salt-water-invasion environment is guaranteed, and meanwhile the cost of the raw materials is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of seawater intrusion prevention and control, in particular to anti-saltwater coating material technology, and in particular to a metal anti-saltwater coating structure resistant to low-saltwater intrusion and a construction method thereof. Background Art

[0002] According to domestic and foreign statistics, the economic losses caused by structural corrosion and durability diseases are huge. From the 1970s to the 1980s, the economic losses caused by structural corrosion in the United States reached 70 billion to 168 billion US dollars. The 11 reinforced concrete viaducts on the central ring expressway of the Isle of England, UK, cost 28 million pounds to build, and the cost of repair due to corrosion was 45 million pounds, about 1.6 times the initial cost; in the subsequent 15 years, it continued to cost about 120 million pounds, which is close to 6 times the original project cost. Foreign scholars use the "five-fold law" to quantitatively describe the importance of considering structural durability in the design stage, that is, if $1 is saved in anti-corrosion / protection during the structural design stage, then when steel corrosion is found, remedial measures will add $5 in repair costs; when concrete cracks along the reinforcement, additional measures will add $25 in repair costs; when the structure suffers serious durability damage, additional measures will add $125 in repair costs. It can be seen from this that in the corrosive environment of seawater intrusion, the durability of metal structures should be taken seriously during the design process, otherwise the economic losses caused by repairs and reinforcements during the later operation and maintenance will be difficult to predict. Therefore, in the prevention and control projects of seawater intrusion, anti-salt and anti-corrosion treatment of metal structures is also necessary.

[0003] In the prior art, anti-salt coating materials are used to treat metal materials with anti-salt and anti-corrosion, which has good anti-salt and anti-corrosion effects, low cost, simple construction, and easy later repair. Therefore, it is one of the more commonly used metal anti-salt and anti-corrosion treatment methods. However, most of the existing anti-salt and anti-corrosion coatings are designed based on highly corrosive environments. Although they have excellent anti-corrosion effects, their costs are relatively high, and their service life is affected by adhesion. The difference in service life in environments with different degrees of corrosion is not large, so they are not suitable for low-salt water (salinity less than 2‰) invading metal saltwater projects. Therefore, it is of great engineering significance to develop a saltwater coating that is suitable for low-salt water (salinity less than 2‰) invading metal saltwater projects, and has low cost and good adhesion. Summary of the invention

[0004] The purpose of the present invention is to provide a metal anti-salt coating structure for low salt water intrusion and a construction method thereof, in order to solve the problems of high cost and poor adhesion of the existing anti-salt coating used for anti-salt engineering of metal intrusion by low salt water (salinity less than 2‰).

[0005] In order to achieve the above-mentioned invention object, the present invention provides a metal anti-salt coating structure with low salt water intrusion, which comprises a bottom layer with a thickness of 100-150 μm, a middle layer with a thickness of 150-250 μm and a surface layer with a thickness of 50-100 μm;

[0006] The bottom layer is formed by coating and curing graphene zinc powder paint; the middle layer is formed by coating and curing epoxy resin paint; and the surface layer is formed by coating and curing acrylic polyurethane paint.

[0007] The graphene zinc powder coating is prepared from the following raw materials in parts by weight: 25-40 parts of epoxy resin, 5-10 parts of graphene powder, 30-45 parts of polyaminoamide resin, 3-8 parts of thixotropic agent, 2-5 parts of filler, 1-2 parts of auxiliary agent and 10-15 parts of zinc powder; the filler is glass fiber or barium sulfate fiber;

[0008] The epoxy resin coating is prepared from the following raw materials in parts by weight: 40-60 parts of epoxy resin, 5-10 parts of polyaminoamide, 20-30 parts of solvent, 5-10 parts of silicon dioxide powder, 3-6 parts of curing agent, 1-3 parts of accelerator, and 1-2 parts of auxiliary agent;

[0009] The acrylic polyurethane coating is prepared from the following raw materials in parts by weight: 60-85 parts of hydroxy acrylic resin, 20-30 parts of solvent, 10-20 parts of silicon dioxide powder, 0.2-1 parts of auxiliary agent, and 15-20 parts of hexamethylene diisocyanate.

[0010] The present invention discloses a metal salt-proof coating structure with low salt-water intrusion. By targetedly designing a coating formula and coordinating the thicknesses of various coatings, better physical anchoring and chemical bonding effects can be formed between various coatings, thereby significantly improving the adhesion of the coating structure on the metal material and the bonding force between the coatings, and significantly improving the service life of the coating structure. At the same time, conventional raw materials are selected from a wide range of sources, which not only ensures the anti-corrosion effect in a low salt-water intrusion environment, but also significantly reduces the cost of raw materials, thereby achieving an optimal balance between the best anti-corrosion effect, the lowest cost and the optimal service life of the salt-proof coating in a low-concentration salt-water environment.

[0011] Among them, adding fiber material as filler to the bottom layer can improve the toughness of the coating and increase the roughness of the coating surface, which is beneficial to the physical anchoring effect of the middle layer on the bottom layer and improves the bonding force between the bottom layer and the middle layer; preferably, the diameter of the glass fiber or barium sulfate fiber is 10-15μm and the length is 50-100μm; the preferred fiber size has better dispersibility and can also avoid reducing the bonding force between the bottom layer and the metal surface.

[0012] Among them, the addition of silica powder increases the weather resistance and corrosion resistance of the coating, and can also better fit into the pores formed on the surface of the underlying fiber filler, thereby achieving the best anchoring effect and improving the bonding force between coatings; preferably, the particle size of the silica powder is 0.1-1.0μm; the preferred silica powder particle size has better dispersibility and better effect on improving the interlayer bonding force; more preferably, the particle size of the silica powder is 0.2-0.5μm.

[0013] Wherein, preferably, the thixotropic agent is polyamide wax or polyethylene wax.

[0014] Among them, preferably, the curing agent is at least one of diethylenetriamine, triethylenetetramine, polyetheramine, hydrogenated toluene diamine, and cyclohexyldimethylamine.

[0015] Preferably, the accelerator is one of dimethylimidazole and phenylaminoformylimidazole.

[0016] Wherein, the solvent is at least one of xylene, dimethyl adipate and butyl acetate.

[0017] Wherein, the auxiliary agent is a leveling agent and / or a dispersant; the leveling agent is a silicone resin, such as SH-450; the dispersant is polyvinyl alcohol and / or a quaternary ammonium salt, such as hexadecyltrimethylammonium bromide.

[0018] Among them, the graphene zinc powder coating is prepared by mixing and stirring the above-mentioned corresponding raw materials according to components; the epoxy resin coating is prepared by mixing and stirring the above-mentioned corresponding raw materials according to components; and the acrylic polyurethane coating is prepared by mixing and stirring the above-mentioned corresponding raw materials according to components.

[0019] In order to achieve the above-mentioned purpose of the invention, further, the present invention also provides a construction method of a metal anti-saltwater coating structure with low salt water intrusion, comprising the following steps: coating the graphene zinc powder coating on the surface of the metal material to be anti-corrosion, curing it at a temperature of 10-35°C for 2-3h to form a base layer, and then coating the epoxy resin coating on the base layer; after the epoxy resin coating is cured at a temperature of 10-35°C for 1-2h to form a middle layer, then coating the middle layer with acrylic polyurethane coating, and after the graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low salt water intrusion is obtained.

[0020] The invention discloses a construction method for a metal anti-saltwater coating structure with low saltwater intrusion. By controlling the curing time and temperature of a graphene zinc powder coating and an epoxy resin coating, each coating is compounded before being completely cured, thereby better forming chemical bonds during the curing process and significantly improving the bonding strength between each layer. The construction method is simple to operate and has a controllable process. The formed anti-saltwater coating structure has stable performance and is suitable for large-scale construction of anti-saltwater coating structures.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The metal anti-salinity coating structure of the present invention, through targeted design of coating formula and coordinated coordination of coating thicknesses, enables better physical anchoring and chemical bonding effects to be formed between coatings, thereby significantly improving the adhesion of the coating structure on the metal material and the bonding force between coatings, and significantly improving the service life of the coating structure.

[0023] 2. In the metal anti-salinity coating structure of the present invention, each layer of coating is made of conventional raw materials with a wide range of sources. While ensuring the anti-corrosion effect in a low-salinity intrusion environment, it also significantly reduces the cost of raw materials, thereby achieving the best balance between the best anti-corrosion effect, lowest cost and optimal service life of the anti-salinity coating in a low-concentration salt water environment.

[0024] 3. The construction method of the metal anti-salinity coating structure of the present invention controls the curing time and temperature of the graphene zinc powder coating and the epoxy resin coating, so that each coating is compounded before it is completely cured, thereby better forming chemical bonds during the curing process and significantly improving the bonding strength between the layers. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments. However, it should not be understood that the scope of the above subject matter of the present invention is limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.

[0026] Embodiment 1:

[0027] A metal anti-salt coating structure with low salt water intrusion, comprising a bottom layer with a thickness of 120 μm, a middle layer with a thickness of 200 μm and a surface layer with a thickness of 80 μm;

[0028] The bottom layer is formed by coating and curing the graphene zinc powder coating; the graphene zinc powder coating is prepared by mixing the following raw materials in parts by weight: 35 parts of epoxy resin, 8 parts of graphene powder, 38 parts of polyaminoamide resin, 5 parts of polyamide wax or polyethylene wax, 3 parts of glass fiber (diameter 12 μm, length 80 μm), 1 part of leveling agent (SH-450) and 12 parts of zinc powder;

[0029] The middle layer is formed by coating and curing the epoxy resin coating; the epoxy resin coating is prepared by mixing the following raw materials in parts by weight: 50 parts of epoxy resin, 8 parts of polyaminoamide, 25 parts of xylene, 8 parts of silicon dioxide powder (particle size is 0.5 μm), 5 parts of curing agent (triethylenetetramine), 2 parts of accelerator (phenylaminoformyl imidazole), 1 part of leveling agent (SH-450) and 1 part of dispersant (hexadecyltrimethylammonium bromide);

[0030] The surface layer is formed by coating and curing the acrylic polyurethane coating; the acrylic polyurethane coating is prepared by mixing the following raw materials in parts by weight: 75 parts of hydroxy acrylic resin, 25 parts of hydrogenated toluene diamine, 15 parts of silica powder (with a particle size of 0.5 μm), 1 part of leveling agent (SH-450), and 18 parts of hexamethylene diisocyanate;

[0031] The construction method comprises the following steps: coating the graphene zinc powder coating on the surface of the metal material to be anti-corrosion, curing it at a temperature of 25°C for 2.5 hours to form a base layer, and then coating the base layer with epoxy resin coating; after the epoxy resin coating is cured at a temperature of 25°C for 1.5 hours to form a middle layer, coating the middle layer with acrylic polyurethane coating, and after the graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low saltwater intrusion is obtained.

[0032] Embodiment 2:

[0033] A metal anti-salt coating structure with low salt water intrusion, comprising a bottom layer with a thickness of 150 μm, a middle layer with a thickness of 150 μm and a surface layer with a thickness of 50 μm;

[0034] The bottom layer is formed by coating and curing the graphene zinc powder coating; the graphene zinc powder coating is prepared by mixing the following raw materials in parts by weight: 40 parts of epoxy resin, 10 parts of graphene powder, 30 parts of polyaminoamide resin, 8 parts of polyamide wax, 2 parts of barium sulfate fiber (diameter 10 μm, length 50 μm), 2 parts of leveling agent (SH-450) and 15 parts of zinc powder;

[0035] The middle layer is formed by coating and curing the epoxy resin coating; the epoxy resin coating is prepared by mixing the following raw materials in parts by weight: 60 parts of epoxy resin, 10 parts of polyaminoamide, 20 parts of butyl acetate, 5 parts of silicon dioxide powder (particle size is 1.0 μm), 6 parts of curing agent (cyclohexyldimethylamine), 1 part of accelerator (dimethylimidazole), and 1 part of dispersant (polyvinyl alcohol);

[0036] The surface layer is formed by coating and curing the acrylic polyurethane coating; the acrylic polyurethane coating is prepared by mixing the following raw materials in parts by weight: 85 parts of hydroxy acrylic resin, 20 parts of (triethylenetetramine), 20 parts of (particle size 0.1 μm) silicon dioxide powder, 1 part of leveling agent (SH-450), and 15 parts of hexamethylene diisocyanate;

[0037] The construction method comprises the following steps: coating the graphene zinc powder coating on the surface of the metal material to be anti-corrosion, curing it at a temperature of 10°C for 3 hours to form a base layer, and then coating the base layer with epoxy resin coating; after the epoxy resin coating is cured at a temperature of 10°C for 2 hours to form a middle layer, coating the middle layer with acrylic polyurethane coating, and after the graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low saltwater intrusion is obtained.

[0038] Embodiment 3:

[0039] A metal anti-salt coating structure with low salt water intrusion, comprising a bottom layer with a thickness of 100 μm, a middle layer with a thickness of 250 μm and a surface layer with a thickness of 100 μm;

[0040] The bottom layer is formed by coating and curing the graphene zinc powder coating; the graphene zinc powder coating is prepared by mixing the following raw materials in parts by weight: 25 parts of epoxy resin, 5 parts of graphene powder, 45 parts of polyaminoamide resin, 3 parts of polyamide wax or polyethylene wax, 2-5 parts of glass fiber (diameter 15 μm, length 100 μm), 2 parts of leveling agent (SH-450) and 10 parts of zinc powder;

[0041] The middle layer is formed by coating and curing the epoxy resin coating; the epoxy resin coating is prepared by mixing the following raw materials in parts by weight: 40 parts of epoxy resin, 5 parts of polyaminoamide, 30 parts of dimethyl adipate, 10 parts of silicon dioxide powder (particle size is 0.1 μm), 3 parts of curing agent (polyether amine), 3 parts of accelerator (dimethyl imidazole), and 2 parts of dispersant (hexadecyl trimethyl ammonium bromide);

[0042] The surface layer is formed by coating and curing the acrylic polyurethane coating; the acrylic polyurethane coating is prepared by mixing the following raw materials in parts by weight: 60 parts of hydroxy acrylic resin, 25 parts of (diethylenetriamine), 10 parts of (particle size 1.0 μm) silicon dioxide powder, 0.2 parts of leveling agent (SH-450), and 20 parts of hexamethylene diisocyanate;

[0043] The construction method comprises the following steps: coating the graphene zinc powder coating on the surface of the metal material to be anti-corrosion, curing it at a temperature of 35°C for 2 hours to form a base layer, and then coating the base layer with epoxy resin coating; after the epoxy resin coating is cured at a temperature of 35°C for 1 hour to form a middle layer, coating the middle layer with acrylic polyurethane coating, and after the graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low saltwater intrusion is obtained.

[0044] Comparative Example 1:

[0045] An anti-salty coating structure, comprising in sequence a bottom layer with a thickness of 100 μm, a middle layer with a thickness of 250 μm and a surface layer with a thickness of 100 μm;

[0046] The bottom layer is formed by coating and curing the graphene zinc powder coating; the graphene zinc powder coating is prepared by mixing the following raw materials in parts by weight: 25 parts of epoxy resin, 5 parts of graphene powder, 45 parts of polyaminoamide resin, 3 parts of polyamide wax or polyethylene wax, 2-5 parts of barium sulfate powder (particle size of 50 μm), 2 parts of leveling agent (SH-450) and 10 parts of zinc powder;

[0047] The middle layer and the surface layer are the same as those in Example 1;

[0048] The construction method is the same as that of Example 1.

[0049] Comparative Example 2

[0050] An anti-salty coating structure, comprising in sequence a bottom layer with a thickness of 100 μm, a middle layer with a thickness of 250 μm and a surface layer with a thickness of 100 μm;

[0051] Wherein, the bottom layer is the same as that in Example 1;

[0052] The middle layer is formed by coating and curing the epoxy resin coating; the epoxy resin coating is prepared by mixing the following raw materials in parts by weight: 40 parts of epoxy resin, 5 parts of polyaminoamide, 30 parts of dimethyl adipate, 10 parts of glass fiber (diameter 15 μm, length 100 μm), 3 parts of curing agent (polyether amine), 3 parts of accelerator (dimethylimidazole), and 2 parts of dispersant (hexadecyltrimethylammonium bromide);

[0053] The surface layer is the same as that of Example 1;

[0054] The construction method is the same as that of Example 1.

[0055] Comparative Example 3

[0056] An anti-salt coating structure, comprising in sequence a bottom layer with a thickness of 120 μm, a middle layer with a thickness of 200 μm and a surface layer with a thickness of 80 μm;

[0057] Among them, the bottom layer, middle layer and surface layer are the same as those in Example 1;

[0058] The construction method comprises the following steps: coating the graphene zinc powder coating on the surface of the metal material to be anti-corrosion, curing it at a temperature of 25°C for 24 hours to form a base layer, and then coating the base layer with epoxy resin coating; after the epoxy resin coating is cured at a temperature of 25°C for 1.5 hours to form a middle layer, coating the middle layer with acrylic polyurethane coating, and after the graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low saltwater intrusion is obtained.

[0059] Comparative Example 4

[0060] An anti-salt coating structure, comprising in sequence a bottom layer with a thickness of 120 μm, a middle layer with a thickness of 200 μm and a surface layer with a thickness of 80 μm;

[0061] Among them, the bottom layer, middle layer and surface layer are the same as those in Example 1;

[0062] The construction method comprises the following steps: coating the graphene zinc powder coating on the surface of the metal material to be anti-corrosion, curing it at a temperature of 25°C for 0.5h, and then coating the epoxy resin coating on the bottom layer; after the epoxy resin coating is cured at a temperature of 25°C for 0.5h, coating the acrylic polyurethane coating on the middle layer, and after the graphene zinc powder coating, epoxy resin coating and acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low saltwater intrusion is obtained.

[0063] Comparative Example 5

[0064] An anti-salt coating structure, comprising in sequence a bottom layer with a thickness of 120 μm, a middle layer with a thickness of 200 μm and a surface layer with a thickness of 80 μm;

[0065] Wherein, the bottom layer is the same as that in Example 1;

[0066] The middle layer is coated and cured by acrylic polyurethane coating; the acrylic polyurethane coating is prepared by mixing the following raw materials in parts by weight: 75 parts of hydroxy acrylic resin, 25 parts of hydrogenated toluene diamine, 15 parts of silica powder (particle size is 0.5 μm), 1 part of leveling agent (SH-450), and 18 parts of hexamethylene diisocyanate;

[0067] The surface layer is formed by coating and curing the epoxy resin coating; the epoxy resin coating is prepared by mixing the following raw materials in parts by weight: 50 parts of epoxy resin, 8 parts of polyaminoamide, 25 parts of xylene, 8 parts of silicon dioxide powder (particle size is 0.5 μm), 5 parts of curing agent (triethylenetetramine), 2 parts of accelerator (phenylaminoformyl imidazole), 1 part of leveling agent (SH-450) and 1 part of dispersant (hexadecyltrimethylammonium bromide);

[0068] The construction method is the same as that of Example 1.

[0069] Comparative Example 6

[0070] JTS153-3-2007 anti-corrosion coating system, in which the bottom layer is 100μm thick epoxy zinc-rich primer, the middle layer is 400μm thick epoxy micaceous iron intermediate paint; the surface layer is 300μm thick acrylic aliphatic polyurethane topcoat.

[0071] Experimental example:

[0072] The anti-salty coating structures in Examples 1-3 and Comparative Examples 1-6 were subjected to adhesion (GB / T 5210), salt water resistance (GB / T9274), and artificial accelerated aging (GB / T 1865) tests, and their costs were estimated. The results are shown in the following table:

[0073]

[0074] Analysis of the above experimental results shows that the present invention, through targeted design of coating formula and coordinated coordination of coating thicknesses, enables better physical anchoring and chemical bonding effects to be formed between coatings, thereby significantly improving the adhesion of the coating structure on the metal material and the bonding force between coatings, and significantly improving the service life (anti-aging and salt water resistance) of the coating structure; at the same time, each layer of coating is made of conventional raw materials with a wide range of sources, which not only ensures the anti-corrosion effect in a low-salt water intrusion environment, but also significantly reduces the cost of raw materials, thereby achieving the best balance between the best anti-corrosion effect, the lowest cost and the best service life of the anti-salt water coating in a low-concentration salt water environment, and is suitable for large-scale promotion and application.

Claims

1. A metal anti-salt coating structure with low salt water intrusion, characterized in that: It comprises in sequence a bottom layer with a thickness of 100-150 μm, a middle layer with a thickness of 150-250 μm and a surface layer with a thickness of 50-100 μm; The bottom layer is formed by coating and curing graphene zinc powder paint; the middle layer is formed by coating and curing epoxy resin paint; and the surface layer is formed by coating and curing acrylic polyurethane paint. The graphene zinc powder coating is prepared from the following raw materials in parts by weight: 25-40 parts of epoxy resin, 5-10 parts of graphene powder, 30-45 parts of polyaminoamide resin, 3-8 parts of thixotropic agent, 2-5 parts of filler and 10-15 parts of zinc powder; the thixotropic agent is polyamide wax or polyethylene wax; the filler is glass fiber or barium sulfate fiber, and 1-2 parts of additives; The epoxy resin coating is prepared from the following raw materials in parts by weight: 40-60 parts of epoxy resin, 5-10 parts of polyaminoamide, 20-30 parts of solvent, 5-10 parts of silicon dioxide powder, 3-6 parts of curing agent, 1-3 parts of accelerator, and 1-2 parts of auxiliary agent; The acrylic polyurethane coating is prepared from the following raw materials in parts by weight: 60-85 parts of hydroxy acrylic resin, 20-30 parts of solvent, 10-20 parts of silicon dioxide powder, 0.2-1 parts of auxiliary agent, and 15-20 parts of hexamethylene diisocyanate.

2. The metal anti-salt coating structure according to claim 1, characterized in that: The glass fiber or barium sulfate fiber has a diameter of 10-15 μm and a length of 50-100 μm.

3. The metal anti-salt coating structure according to claim 1 is characterized in that: The particle size of the silicon dioxide powder is 0.1-1.0 μm.

4. The metal anti-salt coating structure according to claim 3 is characterized in that: The particle size of the silicon dioxide powder is 0.2-0.5 μm.

5. The metal anti-salt coating structure according to claim 1, characterized in that: The thixotropic agent is polyamide wax or polyethylene wax.

6. The metal anti-salt coating structure according to claim 1, characterized in that: The curing agent is at least one of diethylenetriamine, triethylenetetramine, polyetheramine, hydrogenated toluene diamine and cyclohexyl dimethylamine.

7. The metal anti-salt coating structure according to claim 1 is characterized in that: The accelerator is one of dimethyl imidazole and phenylamino formyl imidazole.

8. The metal anti-salt coating structure according to claim 1, characterized in that: The solvent is at least one of xylene, dimethyl adipate and butyl acetate.

9. The metal anti-salt coating structure according to any one of claims 1 to 8, characterized in that: The auxiliary agent is a leveling agent and / or a dispersant.

10. A construction method for the metal anti-salinity coating structure according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: coating a graphene zinc powder coating on the surface of a metal material to be anticorrosive, curing the coating at a temperature of 10-35°C for 2-3h to form a bottom layer, and then coating an epoxy resin coating on the bottom layer; curing the epoxy resin coating at a temperature of 10-35°C for 1-2h to form a middle layer, and then coating the middle layer with an acrylic polyurethane coating; after the graphene zinc powder coating, the epoxy resin coating and the acrylic polyurethane coating are completely cured, a metal anti-saltwater coating structure with low saltwater intrusion is obtained.

Citation Information

Patent Citations

  • Anti-corrosive coating for surface layer of electrical equipment and preparation method ofanti-corrosive coating

    CN108395785A

  • Special graphene anticorrosive coating material for transformer shell, and preparation method thereof

    CN111040582A

  • Graphite alkene heavy anti -corrosion coating scribbles layer structure

    CN206736150U

  • Modified graphene and graphene nanoplatelet for Anti-corrosion coatings

    WO2021158590A1